(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
The article examines the role of natural science in forming scientific thinking among primary school students. It analyzes the developmental characteristics of younger learners, explores the pedagogical conditions necessary for effective natural science education, and highlights the importance of inquiry-based learning, observation, experiments and problem-solving tasks. The study emphasizes that natural science contributes to cognitive activity, curiosity and the ability to establish causal relationships. The author concludes that natural science lessons, when organized correctly, significantly shape analytical, research and reflective skills at an early age.